2015
DOI: 10.1016/j.jpowsour.2015.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature rechargeable magnesium batteries with sulfur-containing composite cathodes prepared from elemental sulfur and bis(alkenyl) compound having a cyclic or linear ether unit

Abstract: Room temperature rechargeable magnesium (Mg) batteries are constructed from Mg as a negative material, sulfur (S)-containing composite prepared from elemental sulfur and the bis(alkenyl) compound having a crown ether unit (BUMB18C6) or linear ether unit (UOEE) as a positive material and the simple electrolyte (0.7 mol dm-3 Mg[N(SO 2 CF 3) 2 ] 2-triglyme (G3) solution). The reaction between molten S and the bis(alkenyl) compound (BUMB18C6 or UOEE) provides the sulfur-containing composite, S-BUMB18C6 or S-UOEE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 23 publications
0
35
0
2
Order By: Relevance
“…This approach may also be useful with metal oxide conversion cathodes such as MnO 2 .V ardar et al have recently shown am agnesium-oxygen cell utilizing the MACC electrolyte.T his battery exhibited high discharge capacity but poor capacity retention. [42,47,[116][117][118][119] An alternative approach to suppressing the polysulfide shuttle mechanism is to incorporate the sulfur into amaterial which prevents polysulfide species dissolution during discharge.N uLi et al [120] prepared carbyne polysulfide by heating carbyne and sulfur,a nd evaluated its performance in 0.25 m Mg(AlCl 2 EtBu) 2 /THF electrolyte.T his material consisted of asp 2 carbon skeleton with sulfur-containing side chains.T he theoretical capacity of this carbyne polysulfide was 609 mAh g À1 and cell discharge at relatively low rate exhibited two voltage regions,arelatively flat plateau at 1.6 V (0 to % 200 mAh g À1 )and asloping portion from 1.1 Vto0.5 V (200-328 mAh g À1 ), indicative of the existence of two different discharge processes.C apacity declined significantly at higher discharge rates.I taoka et al [121] prepared composites of sulfur and ether-containing molecules and evaluated their electrochemical performance in Mg(TFSA) 2 in THF or acetonitrile electrolytes.F irst cycle discharge capacities in the range of 500-600 mAh g À1 were measured, but rapid capacity fade was observed as early as the second cycle and by 10 cycles the capacity was typically < 100 mAh g À1 .C omposites with cyclic (crown) ether-containing molecules exhibited Challenges with Mg/metal halide batteries include irreversibility of the discharge product (in the case of metal fluorides such as CuF 2 )and solubility of the discharge product in the electrolyte (in the case of metal chlorides such as AgCl). [115] Theu se of sulfur in ar echargeable Mg battery requires the use of nonnucleophilic electrolytes rather than Grignard-based electrolytes which have dominated this field.…”
Section: Conversion Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach may also be useful with metal oxide conversion cathodes such as MnO 2 .V ardar et al have recently shown am agnesium-oxygen cell utilizing the MACC electrolyte.T his battery exhibited high discharge capacity but poor capacity retention. [42,47,[116][117][118][119] An alternative approach to suppressing the polysulfide shuttle mechanism is to incorporate the sulfur into amaterial which prevents polysulfide species dissolution during discharge.N uLi et al [120] prepared carbyne polysulfide by heating carbyne and sulfur,a nd evaluated its performance in 0.25 m Mg(AlCl 2 EtBu) 2 /THF electrolyte.T his material consisted of asp 2 carbon skeleton with sulfur-containing side chains.T he theoretical capacity of this carbyne polysulfide was 609 mAh g À1 and cell discharge at relatively low rate exhibited two voltage regions,arelatively flat plateau at 1.6 V (0 to % 200 mAh g À1 )and asloping portion from 1.1 Vto0.5 V (200-328 mAh g À1 ), indicative of the existence of two different discharge processes.C apacity declined significantly at higher discharge rates.I taoka et al [121] prepared composites of sulfur and ether-containing molecules and evaluated their electrochemical performance in Mg(TFSA) 2 in THF or acetonitrile electrolytes.F irst cycle discharge capacities in the range of 500-600 mAh g À1 were measured, but rapid capacity fade was observed as early as the second cycle and by 10 cycles the capacity was typically < 100 mAh g À1 .C omposites with cyclic (crown) ether-containing molecules exhibited Challenges with Mg/metal halide batteries include irreversibility of the discharge product (in the case of metal fluorides such as CuF 2 )and solubility of the discharge product in the electrolyte (in the case of metal chlorides such as AgCl). [115] Theu se of sulfur in ar echargeable Mg battery requires the use of nonnucleophilic electrolytes rather than Grignard-based electrolytes which have dominated this field.…”
Section: Conversion Cathodesmentioning
confidence: 99%
“…Thea uthors of this study concluded that incorporation of an electrolyte solvent or solvent blend that minimizes or eliminates polysulfide solubility would significantly improve performance of Mg-S batteries.Recent studies have demonstrated an improvement in both cycle life and rate capability. [42,47,[116][117][118][119] An alternative approach to suppressing the polysulfide shuttle mechanism is to incorporate the sulfur into amaterial which prevents polysulfide species dissolution during discharge.N uLi et al [120] prepared carbyne polysulfide by heating carbyne and sulfur,a nd evaluated its performance in 0.25 m Mg(AlCl 2 EtBu) 2 /THF electrolyte.T his material consisted of asp 2 carbon skeleton with sulfur-containing side chains.T he theoretical capacity of this carbyne polysulfide was 609 mAh g À1 and cell discharge at relatively low rate exhibited two voltage regions,arelatively flat plateau at 1.6 V (0 to % 200 mAh g À1 )and asloping portion from 1.1 Vto0.5 V (200-328 mAh g À1 ), indicative of the existence of two different discharge processes.C apacity declined significantly at higher discharge rates.I taoka et al [121] prepared composites of sulfur and ether-containing molecules and evaluated their electrochemical performance in Mg(TFSA) 2 in THF or acetonitrile electrolytes.F irst cycle discharge capacities in the range of 500-600 mAh g À1 were measured, but rapid capacity fade was observed as early as the second cycle and by 10 cycles the capacity was typically < 100 mAh g À1 .C omposites with cyclic (crown) ether-containing molecules exhibited Challenges with Mg/metal halide batteries include irreversibility of the discharge product (in the case of metal fluorides such as CuF 2 )and solubility of the discharge product in the electrolyte (in the case of metal chlorides such as AgCl). Zhang,L ing, and Mizuno [122] evaluated the performance of AgCl as ac athode with aM ga node in APC/THF electrolyte.T he cell discharged at % 2.0 Vw ith ac athode capacity of about 150 mAh g À1 at low rate (0.1C) and maintained > 100 mAh g À1 at rates up to 10C after an initial activation cycle.H owever,a sw ith many other Mg cathode materials the capacity declined rather rapidly at first, stabilizing at % 60 mAh g À1 at 0.5C.B ecause of this capacity decline and the fact that sufficient electrolyte must be present in the battery to accommodate the MgCl 2 discharge product, the energy density of this battery is rather low.O verall, the difficulty of demonstrating practical metal halide conversion cathodes for rechargeable Mg batteries appears to be relatively high.…”
Section: Conversion Cathodesmentioning
confidence: 99%
“…Itaoka et al prepared sulfur composites with S and bis(alkenyl) compound with a crown or linear ether unit. [83] With the electrolyte solution of Mg(TFSI) 2 in THF or CH 3 CN, the cell delivered the first discharge capacity of ∼600 mAh/g, but rapid capacity drop Recently, Zhang et al prepared the so-called boron-centered anion-based magnesium (BCM) electrolyte and examined its utility for Mg-Se and Mg-S batteries. [79] A first discharge capacity of 1081 mAh/g was measured for the S cathode using the electrolyte with a surprisingly low Mg concentration of 0.05 M. A relatively flat discharge voltage plateau at about 1.1 V was reported.…”
Section: Conductive Salt-based Electrolytesmentioning
confidence: 99%
“…Itaoka et al[121] erzeugten Komposite aus Schwefel und Ethermolekülen, deren elektrochemische Leistung in Mg(TFSA) 2 sie in THF und Acetonitril testeten. Die theoretische Kapazitätd ieser Carbinpolysulfide war 609 mAh g À1 ,u nd die Zellentladung bei relativ kleiner Rate ergab zwei Spannungsbereiche,e in flaches Plateau bei 1.6 V(0bis etwa 200 mAh g À1 )und einen abfallenden Bereich zwischen 1.1 Vu nd 0.5 V( 200-328 mAh g À1 ).…”
unclassified
“…Dieser Befund deutet auf zwei verschiedene Entladeprozesse hin. Die Kapazitätv erringerte sich bei hç-Itaoka et al[121] erzeugten Komposite aus Schwefel und Ethermolekülen, deren elektrochemische Leistung in Mg(TFSA)2 sie in THF und Acetonitril testeten. Die Anfangsentladekapazitätl ag im Bereich von 500-600 mAh g À1 ,doch schon im zweiten Zyklus setzte ein rapider Kapazitätsverlust ein, und die typische Kapazitätn ach zehn Zyklen war < 100 mAh g À1 .K omposite mit Molekülen, die cyclische (Kronen-)Ether enthalten, hatten eine bessere Kapazitätsretention als solche mit linearen Ethern, und im Gegensatz zu den typischen experimentellen Resulten mit anderen Kathodenmaterialien waren Elektrolyte mit Tr iglyme solchen mit Acetonitril überlegen.…”
unclassified